Synthesising enablers and barriers to hepatocellular carcinoma surveillance-A systematic review of qualitative findings. - Dina Moussa; Joan Ericka Flores; Joseph S Doyle; Marno Ryan; Jack Wallace; Jessica Howell (PLoS ONE)
Background & aims This systematic literature review of qualitative findings aims to identify the perceived barriers and enablers for hepatocellular carcinoma (HCC) surveillance from patient and clinician perspectives. Methods A systematic search of databases using key term combinations with the following inclusion criteria: 1) qualitative and quantitative (survey) studies exploring barriers and enablers of HCC surveillance, and 2) qualitative and quantitative (survey) studies exploring barriers and enablers of enagagement in clinical care for patients with cirrhosis and/or viral hepatitis. Results The search returned 445 citations: 371 did not meet the study criteria and were excluded. 74 studies proceeded to full-text review, leading to 21 included studies (15 studies from searching with a further six studies from citation review) progressing to data extraction by two independent reviewers. Results from studies exploring patients' perspectives reinforce that barriers are experienced by patients across different health settings, cultures, and regions. Logistical barriers including costs and transportation, and knowledge/awareness barriers were commonly identified. Studies that included clinician perspectives highlighted the need for healthcare provider education and system-level interventions to optimize HCC surveillance uptake in clinical practice. Conclusion These findings highlight the critical need for interventions that enable engagement in HCC surveillance in health services.